Determining the Dose-Response Effects of a Modified Corn Protein Product in Nursery Pig Diets - Paula Giacomini; Jason C. Woodworth; Katelyn N. Gaffield; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Keith Mertz; John F. Patience (Kansas Agricultural Experiment Station Research Reports, 2025)
This experiment was conducted to determine the dose-response effects of a modified corn protein product (MCP; Cargill Starches, Sweeteners, & Texturizers, Blair, Nebraska) on growth performance, fecal dry matter, removals and mortalities, and apparent total tract digestibility (ATTD) of energy in nursery pigs. A total of 320 weanling pigs (DNA 600 × 241; initially 12.5 lb) were used in a 42-d growth study. Pigs were weaned at approximately 18 d of age, randomly allotted to pens in light (10.8 lb) or heavy (14.5 lb) weight blocks, and then pens were allotted to one of four dietary treatments in a completely randomized block design. There were five pigs per pen and 16 pens per treatment across two barns. Dietary treatments consisted of 0, 7.5, 10.0, and 12.5% MCP in phase 1 and 0, 2.5, 5.0, and 7.0 % MCP in phase 2. Modified corn protein replaced enzymatically treated soybean meal, conventional soybean meal and feed-grade amino acids in the control diet. Treatment diets were balanced for amino acids and minerals, but not energy, and fed in two dietary phases from d 0 to 10 and d 10 to 24, respectively, followed by a common phase 3 corn-SBM-based diet that did not contain MCP and was fed for the remainder of the trial. The percentage of pigs that lost weight on d 3 increased (linear, P = 0.045) as MCP increased. From d 0 to 10, ADG and d 10 BW decreased (quadratic, P < 0.05) and F/G worsened (linear, P = 0.002) as MCP increased, with the largest difference occurring when MCP increased from 10.0 to 12.5% of the diet. From d 10 to 24, ADG (quadratic, P = 0.086) and ADFI (quadratic, P = 0.023) increased then decreased as MCP increased, with the best performance observed at 2.5% MCP. Day 24 BW tended to decrease (linear, P = 0.064) as MCP increased. From d 24 to 42 when all pigs were fed a common diet, no differences in performance were observed. Overall, there were no ADG or ADFI effects observed, but pigs fed increasing MCP had poorer (linear, P = 0.042) F/G. Fecal DM was not affected by dietary treatment on d 10, but increased then decreased on d 20 (quadratic, P = 0.016) as MCP increased, with the greatest DM observed in pigs fed 5% MCP. In summary, increasing MCP in early nursery diets reduced ADG and worsened F/G. However, in phase 2, when added MCP was reduced, ADG and ADFI, as well as fecal DM, increased then decreased with increasing MCP. For the overall study, increasing MCP had no effects on ADG or ADFI, but worsened F/G, which might reflect the lower dietary ME and NE as MCP increased.
Keywords: corn protein; nursery pigs; soybean meal